From Plant to Patient: A Historical Perspective and Review of Selected Medicinal Plants in Dermatology - Aygun Israyilova; Tsvetomira Zhivkova Peykova; Ben Kittleson; Paul Caleb Sprowl; Taha Osman Mohammed; Cassandra L. Quave (JID Innovations)
Skin conditions are a common health concern faced by patients of all ages. For thousands of years, plants have been used to treat various skin conditions, including acne, vitiligo, and psoriasis, to name a few. Today, with increasing patient preference for natural therapies, modern medicine is now more than ever incorporating age-old knowledge of herbal remedies useful in treating skin conditions into modern-day treatments. This review covers various plant-derived therapeutics (polyphenon E [sincatechins], psoralen, salicylic acid, anthralin, podophyllotoxin, and Filsuvez [birch triterpenes, oleogel-S10]) that have demonstrated scientific evidence of clinical efficacy for dermatologic disorders. The discovery, composition, history of use, and current uses in dermatology are summarized for each botanical ingredient.